Antioxidants: elixir of life - Kalam, Sadaf; Singh, Rupal; Mani, Abin; Patel, Jaswant; Khan, Firoz Naem; Pandey, Adarsh (International Multidisciplinary Research Journal, 2012)
There has been a current upsurge in the medical implications of free radicals and related species during the past several decades. These chemical species are integral components produced during normal biochemical and physiological processes but leads to oxidative stress when produce in excess and causes potential damage to cells. A wide range of non-enzymatic and enzymatic antioxidant defenses exists to counteract the damaging effects of free radicals. There exist epidemiological evidences correlating higher intake of antioxidant rich foodstuffs with greater free radical neutralizing potential to lower incidence of several human morbidities or mortalities. Gene therapy to produce more antioxidants in the body, novel biomolecules and the use of functional foods enriched with antioxidants are milestones to newer approaches to reduce free radical damage. This paper reviews the biology of reactive species, their pathways through which they relate to the pathology of various diseases and discusses the putative roles that antioxidants, from different sources, play in controlling oxidative stress and reduce the incidence of concerned diseases.